Febuxostat in the management of gout: a cost-effectiveness analysis. (3rd March 2016) - Smolen, Lee J.; Gahn, James C.; Mitri, Ghaith; Shiozawa, Aki
Abstract: Objective: To determine the cost-effectiveness of febuxostat vs allopurinol for the management of gout. Methods: A stochastic microsimulation cost-effectiveness model with a US private-payer perspective and 5-year time horizon was developed. Model flow based on guideline and real-world treatment paradigms incorporated gout flare, serum uric acid (sUA) testing, treatment titration, discontinuation, and adverse events, chronic kidney disease (CKD) incidence and progression, and type 2 diabetes mellitus (T2DM) incidence. Outcomes were estimated for the general gout population and for gout patients with CKD stages 3/4. Modeled treatment interventions were daily oral febuxostat 40–80 mg and allopurinol 100–300 mg. Baseline patient characteristics were taken from epidemiologic studies, efficacy data from randomized controlled trials, adverse event rates from package inserts, and costs from the literature, government sources, and expert opinion. Eight clinically-relevant incremental cost-effectiveness ratios were estimated: per patient reaching target sUA, per flare avoided, per CKD incidence, progression, stages 3/4 progression, and stage 5 progression avoided, per incident T2DM avoided, and per death avoided. Results: Five-year incremental cost-effectiveness ratios for the general gout population were $5377 per patient reaching target sUA, $1773 per flare avoided, $221, 795 per incident CKD avoided, $29, 063 per CKD progression avoided, $36, 018 per progression to CKD 3/4 avoided, $71, 426 per progression to CKD 5 avoided, $214, 277 per incident T2DM avoided, and $217, 971 per death avoided. In patients with CKD 3/4, febuxostat dominated allopurinol for all cost-effectiveness outcome measures. Conclusions: Febuxostat may be a cost-effective alternative to allopurinol, especially for patients with CKD stages 3 or 4.